PIXE studies of normal and SIV-infected rhesus macaque tissues: investigations of particulate matter. Issue 1 (1st October 2022) - Whitlow, H J; Henderson, N; Greco, R; Deoli, N; Smith, K M; Morgan, K; Villinger, F
Abstract: Positron Emission Tomography (PET) studies [1] of the evolution of Simian Immunodeficiency Virus (SIV) (the monkey analogue of Human Immunodeficiency Virus (HIV) have revealed that the SIV is localised in different organs at different stages of the infection. Promising routes to completely eradicate the HIV virus particles involve therapies that target the infection at the cellular level. Our previous μ -Particle Induced X-ray Emission ( μ- PIXE) studies revealed very large variations in the contents of heavy minor and trace elements in the jejunum of control and SIV-infected subjects. These variations could be caused by factors such as the histological preparation and particles in chyme. The present work investigates particulate matter observed in the tissue sections in both the control and virus-infected subjects that dominated the variations in the mean elemental content determined by μ -PIXE. Detailed study of the PIXE data suggested the particles with size of 10's of μ m were likely to be made up of agglomerated nano-particles. The measured composition of the particles was consistent with natural calcified particles in the brain (acervuli or "Brain sand"), tattoo ink in a mesenteric lymph node and silica in the liver.